PERSEPSI PENGENDARA SEPEDA MOTOR TERHADAP KESELAMATAN BERLALULINTAS BERDASARKAN THEORY PLANNED BEHAVIOR - Tangkudung, Ellen S.W.; Sampouw, Marcelino; Tjahjono, Tri (Jurnal Transportasi, 2010)
High numbers of dead and injury victims caused by road traffic accident can not be simply ignored. The National Accident data shows high percentage of motorcycle involved in accidents, with data in 2006 show more than 50% of the vehicles involved in accident are motorcycle. Human, vehicle, road, and environmental factors are major factors that cause accidents, but the most dominant factor is humanity. With the concept of "Theory of Planned Behavior", this paper examines how far the community perception, as part of the road users, in this case the motorcyclist, affects the behavior on the aspect of traffic safety. A survey was carried out on motorcyclists who ride through Brigjen Katamso and R. Suprapto streets in Batam. Based on the measurement of 107 respondents, the average value of Attitude (A) is 7.32, Subjective Norm (SN) is 14.78 and the Perceived Behavioral Control (PBC) is 4.22. From the values of A, SN, and PBC, the value obtained by Behavioral Intention (BI) for the motorcyclist in this study area is 8.78. This value indicates that the motorcycle riders have positive perception with medium to weak levels towards the traffic safety. Motorcycle riders actually have a positive perception of the safety aspects of traffic.Keywords: behavior, perception, safety, motorcycle rider